(untitled) (mathematica didactica, 2021)
After using a historical analysis to show that mathematics is not to be understood as a universal model of explanation, but as a perspective of understanding the world which exists alongside others, the author investigates the significance of four approaches to mathematics for the educational process: mathematical procedures; abstract mathematics; applied mathematics; philosophy of mathematics. He seeks to prove each of these approaches necessary,while none of them alone enables determining the importance of mathematics for the education of man. Only the additional examination of the contributions of each of these approaches to succeeding in life (sense of life), reveals the significance of mathematics for education.